2007
DOI: 10.1007/s11832-007-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Relapse rates following staged surgery in the treatment of recalcitrant talipes equinovarus: 9- to 16-year outcome study

Abstract: Purpose We aimed to identify the long-term rate of relapse of deformity in a cohort of children with talipes equinovarus and to correlate it with pre-operative grading. Methods Between 1988 and 1995, 120 club feet in 86 patients were surgically treated. A review at an average follow-up of 11.5 years (range 9-16 years) was performed. Of 59 of the children, 69 feet were assessed clinically and data for the remaining 20 children (30 feet) were obtained from the records. The patients were assessed using the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Scher et al (2004) reported that an initial score of > 5.0 on the Pirani scale and grade IV feet according to the Dimeglio system would indicate that the patient will very likely need PAT. In addition, Uglow et al (2007) reported that a higher grade according to the Dimeglio system indicates a high rate of relapse. This indicates that clubfeet with higher scores, according to these 2 scoring systems, are at risk of having residual equinus deformities even after Ponseti manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scher et al (2004) reported that an initial score of > 5.0 on the Pirani scale and grade IV feet according to the Dimeglio system would indicate that the patient will very likely need PAT. In addition, Uglow et al (2007) reported that a higher grade according to the Dimeglio system indicates a high rate of relapse. This indicates that clubfeet with higher scores, according to these 2 scoring systems, are at risk of having residual equinus deformities even after Ponseti manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Pirani and Dimeglio scoring systems (Dimeglio et al 1995, Pirani et al 2008) are widely used for grading the severity of clubfoot deformities and have very good interobserver reliability (Flynn et al 1998), there have been few reports on the prognostic significance of these scores (Scher et al 2004, Dyer and Davis 2006, Uglow et al 2007). …”
mentioning
confidence: 99%
“…The average follow-up was 11.5 years and the relapse rate was 76%. 9 Gait analysis has been used by some investigators to try to quantify the results of treatment. A case-control study using this technique compared the outcomes of surgical and non-surgical treatment.…”
Section: Why Do I Need To Know About Clubfoot?mentioning
confidence: 99%
“…5 However, recurrence of ICTEV can be seen in up to one-fifth of patients who have had successful conservative treatment. 6 A systematic review by Thomas et al reported that the CTEV relapse rate occurs in up to 67.3% of patients and its positive correlation with follow-up duration, which in most studies was limited to up to 5 years. The same review identified varying definitions of "relapse" between studies.…”
Section: Introductionmentioning
confidence: 99%